2013
DOI: 10.1002/etc.2090
|View full text |Cite
|
Sign up to set email alerts
|

Combined toxicity of polycyclic aromatic hydrocarbons and heavy metals to biochemical and antioxidant responses of free and immobilized Selenastrum capricornutum

Abstract: Abstract-The aquatic environment often contains different groups of contaminants, but their combined toxicity on microalgae has seldom been reported. The present study compared the toxic effects of combined mixed polycyclic aromatic hydrocarbons (PAHs) and heavy metals on growth and antioxidant responses of free and immobilized microalga, Selenastrum capricornutum. Five PAHsphenanthrene, fluorene, fluoranthene, pyrene, and benzo[a]pyrene-and four heavy metals at different concentrations-0.05 to 0.1 mg Cd 2þ ml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 42 publications
(66 reference statements)
0
7
0
Order By: Relevance
“…Meanwhile, the capacity for AC to bind contaminants in soils reduced contaminant availability (as indicated by shoot uptake- Fig 2) in a way not accounted for by the POM extractions (Fig 1), thereby leading to improved shoot growth. Chlorophyll a has previously been used as a biomarker to assess photosynthesis ability in plants and the presence of both PAHs and PTEs has been shown to inhibit photosynthesis (Kummerová et al, 2006;Oleszczuk, 2008;Wang et al, 2013). Chlorophyll a content increased with PB and MB amendment (p<0.05) compared to the control, but not with AC amendment.…”
Section: Plant Parameters As Affected By Sorbent Amendment Applicatiomentioning
confidence: 99%
“…Meanwhile, the capacity for AC to bind contaminants in soils reduced contaminant availability (as indicated by shoot uptake- Fig 2) in a way not accounted for by the POM extractions (Fig 1), thereby leading to improved shoot growth. Chlorophyll a has previously been used as a biomarker to assess photosynthesis ability in plants and the presence of both PAHs and PTEs has been shown to inhibit photosynthesis (Kummerová et al, 2006;Oleszczuk, 2008;Wang et al, 2013). Chlorophyll a content increased with PB and MB amendment (p<0.05) compared to the control, but not with AC amendment.…”
Section: Plant Parameters As Affected By Sorbent Amendment Applicatiomentioning
confidence: 99%
“…Wang et al. [ 83 ] compared the growth and antioxidant responses of free and immobilized microalgae, Selenastrum capricornutum , under combined toxicity of polycyclic aromatic hydrocarbons and heavy metals. They found that immobilized systems can protect microalgal cells against the toxic contaminants and change the synergistic effect of co-contaminants on cells to antagonistic effects.…”
Section: Why Use Immobilized Microalgal Wastewater Treatment Systems?mentioning
confidence: 99%
“…However, owing to heterogeneous cell distribution inside the immobilization carrier, the relatively low mass transfer of CO 2 or nutrients may limit the growth and cell division of the immobilized microalgae. Luckily, many researchers have reported that microalgae can overcome the imposed damage or space limitation caused by toxicity, high cell density, or uneven cell distribution after a long operation [ 73 , 83 , 84 ]. Besides, stock culture management of functional microalgae species is a vital part of microalgal wastewater treatment, which is also another embodiment of the application of microalgal immobilization technology.…”
Section: Why Use Immobilized Microalgal Wastewater Treatment Systems?mentioning
confidence: 99%
See 1 more Smart Citation
“…The total ATPase activity was analyzed according to a procedure described by Dehn et al [22]. Antioxidant responses including the activities of superoxide dismutase (SOD), peroxidase (POD) and glutathione S-transferase (GST) and the content of MDA were determined according to previous studies [18,23]. The activities of the enzymes and the content of MDA were expressed in units per mg of protein (U/mg protein) and g per mg protein, respectively, in order to eliminate the measurement deviation caused by varied extraction efficiency of protein.…”
Section: Analysis Of Atpase Activity and Antioxidant Responsesmentioning
confidence: 99%